Protracted intra- and inter-pluton magmatism during the Acadian orogeny: evidence from new LA-ICP-MS U-Pb zircon ages from northwestern Maine, USA - Gibson, David; Barr, Sandra M.; van Rooyen, Deanne; White, Chris; Pilote, Jean-Luc (Atlantic Geology)

(untitled) (Atlantic Geoscience Society, 2021)
Devonian granitoid plutons comprise a major part of the bedrock of northwestern Maine representing the magmatic expression of the Acadian orogeny in this part of the northern Appalachian orogen. They are petrographically diverse with minerals characteristic of both I- and S-type granites, in some cases within the same intrusion, and some are compositionally zoned. New LA-ICP-MS ages presented here elucidate the timing and duration of this magmatism. The earliest phase of granitoid magmatism began around 410–405 Ma with the emplacement of the Flagstaff Lake Igneous Complex, and the presence of contemporaneous mafic rocks suggests that mantle-derived magmas were also produced at this time. Late Devonian ages, ca. 365 Ma, for many intrusions, such as the Chain of Ponds and Songo plutons, reveal that magmatism continued for 45 million years during which compositionally diverse I- and S-type magmas were produced. In addition, there is evidence that intrusive activity was prolonged within some plutons, for example the Rome-Norridgewock pluton and the Mooselookmeguntic Igneous Complex, with 10–15 myr between intrusive units. The new ages suggest a break in magmatism between 400 Ma and 390 Ma apparently separating Acadian magmatism into early and late pulses. The production of lower crustal I-type magmas appears to have been concentrated later, ca. 380–365 Ma, although several S-type granitoids were also emplaced during this period. These Late Devonian plutons display abundant zircon inheritance with ages around 385 Ma, which suggests that the crust was experiencing enhanced thermal perturbations during this extended timeframe. The new data for granitoid plutons in northwestern Maine are consistent with tectonic models for other parts of Ganderia which propose initial flat slab subduction followed by slab breakoff and delamination.